1994
DOI: 10.3109/00365529409094864
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium paratuberculosis in Intestinal Tissue from Patients with Crohn's Disease Demonstrated by a Nested Primer Polymerase Chain Reaction

Abstract: Whether the presence of M. paratuberculosis is connected to the inflammatory bowel disease or is a mere coincidence cannot be stated. We find this presence interesting and encouraging for further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 29 publications
1
40
0
1
Order By: Relevance
“…4,6,7,9,15,16,19 Other authors have found a variable number of cases, up to 100%, to harbor the organism. 1,3,5,8,[10][11][12][13][14]18 Several reasons may be responsible for the variability in these results. Differences in patient cohorts, techniques, and experimental conditions immediately come to mind.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,6,7,9,15,16,19 Other authors have found a variable number of cases, up to 100%, to harbor the organism. 1,3,5,8,[10][11][12][13][14]18 Several reasons may be responsible for the variability in these results. Differences in patient cohorts, techniques, and experimental conditions immediately come to mind.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,8,[10][11][12][13][14] Thus, the finding of MAP DNA in Crohn's disease, including in paraffin-embedded resection specimens, 1,12 still leaves unanswered the question of whether the organism may be environmentally acquired and nonspecifically present. MAP has been cultured from municipal water supplies 11 and pasteurized milk, 25,26 suggesting that it may be ubiquitously present in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have incorporated the polymerase chain reaction (PCR) into techniques for detection or identification of mycobacteria in for-malin-fixed, paraffin-embedded tissues of humans 2,5,6,[8][9][10][11][12]19,20,22,[24][25][26] There are no reports of use of the technique for diagnosing tuberculosis in animals, but the procedure has been used to identify M. paratuberculosis in cattle with Johne's disease. 21 In this paper, we describe a PCR test that has been very effective for diagnosing tuberculosis using paraffin sections of diagnostic samples submitted as part of the US bovine tuberculosis eradication program.…”
mentioning
confidence: 99%